Phomaderide, a unique (6/5/4/5/6) spiro-cyclic dimer from the desert plant endophytic fungus Phoma betae A. B. Frank (Didymellaceae) - Sun, Hao-Di; Wang, Yan-Duo; Fang, Hui-Qi; Yang, Jian; Hua, Yu-Tong; Ding, Gang; Guo, Lan-Ping (Frontiers in Chemistry, 2025)
IntroductionEndophytic fungi from desert plants are prolific producers of structurally unique stress-responsive metabolites. This study investigates the secondary metabolites of Phoma betae A. B. Frank (Didymellaceae), a desert plant endophytic fungus, aiming to discover novel bioactive compounds through advanced molecular networking strategies.MethodsA building blocks-based molecular network (BBMN) strategy was employed to screen the fungal extract. Target compounds were isolated using silica gel and ODS column chromatography, followed by semi-preparative HPLC purification. Structural elucidation was achieved through comprehensive NMR spectroscopy, mass fragmentation pathway analysis, and electronic circular dichroism (ECD) calculations. Cytotoxicity was evaluated against HeLa and A549 cancer cell lines using CCK-8 assays.ResultsThree compounds were characterized:Phomaderide (3), a unique (6/5/4/5/6) spiro-cyclic dimer formed via stereoselective [2+2] photocycloaddition of two phaeosphaeride A (1) monomers. Its biosynthetic precursor phaeosphaeride A (1). A new hydroxylated analog, phaeosphaeride C (2). Compounds 2 and 3 exhibited moderate cytotoxicity against HeLa (IC50 29.97–39.15 μM) and A549 cells (IC50 30.47–58.33 μM).DiscussionThis work highlights the metabolic versatility of extremophilic fungi, demonstrating Phoma betae's capacity to generate architecturally complex molecules. Phomaderide's unprecedented spiro-cyclic dimer scaffold positions it as a promising lead for anticancer drug discovery, with structural modifications (hydroxylation and dimerization) significantly influencing bioactivity. The BBMN strategy proved effective for targeted isolation of structurally related analogs from complex extracts.